FAILURE OF ENLIGHTENMENT IN MODERN SOCIETY TO REVEAL GHOSTS IN THE DANCING VILLAGE (“DESA PENARI”) BASED ON ADORNO'S CRITICAL THEORY - Denny Yerianto; Puji Lestari; Frengki Napitupulu (International Journal of Social Science, 2025)
The presence of the Enlightenment Era (Aufklarung) in the 18th century which emphasized rationality and reason, has not been able to eliminate the belief in ghosts in modern society. Currently, rationalization of ghosts is often found in books, television, films, and social media. Efforts to rationalize ghosts actually thwart enlightenment and lead modern society into the commodification of ghosts through the culture industry scheme. In Theodor W. Adorno's Critical Theory, the culture industry is always commercially oriented and makes ghosts a commodity to gain profit. The purpose of this study is to reveal why enlightenment has failed again in modern society by dismantling the commodification of ghosts. This study offers a solution to awaken modern society from false consciousness due to the rationalization of ghosts that are bound by the commodification of ghosts. This study is also expected to be able to renew Adorno's Critical Theory in the context of enlightenment in modern society, namely a different society when this theory was first proposed. Methodology of this study is a qualitative study using the netnography method with a critical paradigm. The object is modern society represented in 9,682 comments on the YouTube Channel "Kisah Tanah Jawa" episode "KKN Desa Penari". By using netnography and analysis of modern society conversation themes from the channel, this study shows the existence of sub-themes of standardization, massification, commodification and false consciousness which indicate the presence of the culture industry scheme. This study also shows how ghost symbols in the culture industry scheme have been produced through 4 approaches to ghost symbol production involving the help of science, technology, religion and rationalist narrative construction in forming false consciousness. This study also reveals the active role of modern society in encouraging the formation of ghost commodification. The result of this study show that society plays an important role in efforts to prevent the failure of enlightenment. True enlightenment is only possible if the relationship between text producers, text consumers, and capital owners is no longer dominated by the logic of capitalism. To achieve this, modern society needs to encourage decommodification of every ghost commodification that occurs and always develop critical awareness to reduce the occurrence of domination and exploitation behind the cultural products they consume to prevent the failure of enlightenment.